Nilai Kepuasan Pengunjung Saung Angklung Udjo - Didin Syarifuddin (Media Wisata, 2021)
Customers are important people in business organizations, do not depend on the company, not people for debate, so that customer desires are the company's duty to be realized. The study purpose is to explain customer satisfaction value as an impact of implementing customer value. The verification method is used to explain the effect of customer value on customer satisfaction with regression analysis. The results explain that Saung Angklung Udjo performance art is a traditional art performance producing beautiful tones, can foster audience enjoyment and satisfaction, the impact of the growing value of performing arts, service, personal, image and cost value. The growth in visitor value has an impact on the growth of visitor satisfaction so as to foster knowledge, a sense of pleasure and the return of fresh feeling to people who experience boredom from their daily routines. This is an important aspect in society that can be used as a reference in the process of interaction as well as a pattern of behaviour and group thought patterns that are mutually recognized in travelling